RANCANG BANGUN MESIN PENGIRIS SINGKONG MENGGUNAKAN PENDORONG LEAD SCREW - Muhammad Arief Aldyansyah (2022)
Cassava is a potential material to be used as a snack. Besides its abundant production, the processing process is also quite easy. Departing from there, the author raised the topic of designing a cassava slicing machine with a driving leadscrew. The study begins with consumer needs then initial design, calculations, material selection to tool making. The slicing method use was a vertical rotation slicer using 4 blades with a pusher that is driven by a leadscrew. The pusher uses a leadscrew that is 350 mm long which can push cassava with a length of 260 mm. The results of the cutting force test have an average of 8.20 N. With the required design power of 0.75 HP and the power used to push the material a minimum of 20 watts with a thrust analysis of 3.64 N. After doing the test three times then the average cutting time is 28 seconds, and the average cutting result is 0.496 kg. Then the effective capacity of this machine is 64 kg/hour. From the experimental results, it can be seen that the thickness of the cutting results ranges from 1 mm - 2.5 m